Mampukah Pembangkit Listrik Tenaga Air Mendorong Green Economy untuk Indonesia? - Siti Allifah; Yusman Syaukat; Pini Wijayanti (School of Postgraduate Studies, Diponegoro Univer, 2023)
Attention to the negative impact of economic growth on the environment has emerged in the green economy paradigm. The utilization of hydropower can achieve green energy as part of green econony. To analyze the role of hydropower in driving Indonesia's green energy, the Autoregressive Distributed Lag (ARDL) method was employed. The results show that increased electricity production from hydropower will reduce environmental damage. Meanwhile, the use of fossil fuels will harm the environment for short and long periods. Indonesia is still in a scale of effect because environmental damage indicated by CO2 emission continuously increases due to economic activities. In addition, there is a bidirectional relationship between GDP and CO2 emissions. This means that Indonesia needs a sustainable economic growth. In addition, there is a bidirectional relationship between electricity production from hydropower and CO2 emissions. At the same time, a unidirectional causality presents from GDP to electricity production from hydropower, coal consumption to GDP, and consumption of oil and natural gas to CO2 emissions. The Indonesian government needs to establish policies which reduces consumption of fossil fuels, increases the investors’s interest in renewable energy, and expands the economic capacity to reach the expected turning point of the economic growth.